The Relationship between Knowledge, Attitude, Behaviour, and Personal Hygiene Standard of Food Handler in Installation of Nutrition - Fitria Ayuti; Laras Sitoayu; Sri Iwaningsih (Jurnal Sains Kesehatan, 2018)
Hygiene Personal is health measures in a way to preserve and protect the cleanliness of individual to achieve a personal hygiene standard of food handler. This research is executed in Installation of  Nutrition Cempaka Putih Jakarta Islamic Hospital in April to June 2016. Target of this research to determine the relationship of knowledge, attitudes, behavior and standards of personal hygiene of food handlers in Installation of Nutrition RS Islam Jakarta Cempaka Putih. This research use analytic method with approach of cross sectional and use sampel amount to 58 respondents. This research concluded that knowledge and attitude of personal hygiene of food handlers reside at level of less and goodness, with each percentage (50%), and half of respondents have standards of personal hygiene behavior less (51,7%). There is significant relationship between knowledge, attitudes, behaviors and standards of personal hygiene in Installation of Nutrition RS Islam Jakarta Cempaka Putih. Results of research suggest that conducted the supervision and oversight of all food handlers conducted by the coordinator of the food processing supervisor in overseeing food handlers, so if there are handlers that do not comply with the regulations the given a reprimand. Keywords:  attitudes, behavior, knowledge, standards of  personal hygiene